One pot menthol synthesis via hydrogenations of citral and citronellal over montmorillonite-supported Pd/Ni-heteropoly acid bifunctional catalysts - Shah, Abdul Karim; Maitlo, Ghulamullah; Shah, Aqeel Ahmed; Channa, Iftikhar Ahmed; Kandhro, Ghulam Abbas; Maitlo, Hubdar Ali; Bhatti, Umair Hassan; Shah, Ahmed; Memon, Abdul Qayoom; Jatoi, Abdul Sattar; Park, Yeung Ho (Reaction Kinetics Mechanisms and Catalysis, 2019)
Menthol synthesis is possible through citral and citronellal hydrogenations via following multistage chemical reactions such as hydrogenation and cyclization. This research mainly focuses on a design of selective, active and cost-effective metal-acid (bifunctional) catalysts for menthol production via citral and citronellal hydrogenations. More specifically, Pd and Ni metals were impregnated over acidic support (e.g., hetero-poly acid supported montmorillonite, HPA_MM). The prepared catalysts were characterized by BET, pyridine adsorption and amine titration methods. Some of the most important parameters such as metal type and loading; applied pressure and reaction time have been investigated throughout this work. The obtained results reveals that the 8 wt% Ni-HPA-MM catalyst (Cat-5) has produced 63% menthols (initial reaction rate 0.126mmol/min) from citral hydrogenation (80 degrees C, 1.0MPa) within 24h. Similarly, during lower applied pressure (0.5MPa), the production of menthol was significantly improved (approximately 98% of menthol, initial reaction rate similar to 0.138mmol/min) with the application of 8 wt% Ni-HPA-MM catalyst (Cat-5) in citronellal hydrogenation. Higher menthol selectivity was achieved from both reactions (citral and citronellal hydrogenation) which might be due to the presence of strong Lewis and medium BrOnsted acid sites.
CRIS-Team WoS Importer:2019-10-18